Perceptual strain in a compensable hot environment: Accuracy and clinical correlates. (August 2021) - Weiner, Cynthia M.; Kazman, Josh B.; Abraham, Preetha A.; Deuster, Patricia A.
Abstract: Heat strain monitoring indexes are important to prevent exertional heat illness (EHI) and uncover risk factors. Two indexes are the Physiological Strain Index (PSI) and a subjective PSI analogue, the Perceptual Strain Index (PeSI). The PeSI is a feasible alternative to PSI in field conditions, although the validity has been variable in previous research. However, the PeSI has been rarely examined at a low heat strain with compensable heat stress, such as during a heat tolerance test (HTT). This study evaluated the discrepancy between the maximal PeSI and maximal PSI achieved during a HTT and determined their association with EHI risk factors, including history of EHI, percent body fat (%BF), relative VO2max, fatigue and sleep status (n = 121; 47 without prior EHI, 74 with prior EHI). The PSI was calculated using the change in rectal temperature (Tre ) and heart rate (HR) and PeSI was calculated based on the formula containing thermal sensation (TS), a Tre analogue, and rate of perceived exertion (RPE), a HR analogue. Significant associations were identified between PSI and PeSI and between PSIHR and PeSIHR in the total sample and between PSI and PeSI in the EHI group. Bland-Altman analyses indicated PeSI underestimated PSI in the total sample, PSIHR was greater than PeSIHR, and that PSIcore and PeSIcore were not significantly different, but values varied widely at different heat strains. This indicates the use of RPE underestimates HR and that the accuracy of TS to predict Tre may be subpar. This study also demonstrated that participants with higher %BF have a decreased perception of heat strain and that post-fatigue, sleep status and a prior EHI may increase the perception of heat strain. Overall, these results suggest that PeSI is a poor surrogate for PSI in a compensable heat stress environment at low heat strain. Highlights: There is low validity of the perceived strain index during compensable heat stress at low physical activity. Intrinsic factors (e.g., body fat, previous heat illness) may impact ability to perceive heat strain. Small association between thermal sensation and perceived exertion with core temperature and heart rate in low heat strain.